Psikoedukasi Untuk Meningkatkan Kesehatan Mental dan Self Awareness Masyarakat - Siti Habibah; Ignatius Okta Tricahya Frannes; Nina Fitriani Pujianahum; Nina Perunaziah; Syabina Zidna Fathna; Alvi Resti Agustian; Hilmy Adya Laksana (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
A community service program was held in the village of sukarukun, sukatani district. The village presents several major problems, including a lack of public understanding of the importance of mental health and self-awareness, and a lack of social social skills on how to create an environment that can improve mental health and improve quality of life. Furthermore, communities have not received adequate information on how to improve the ability to deal with mental and emotional disorders or stresses that arise in response to certain situations. The process of enhanced mental health and self-awareness is carried out through psychoeducation or socialization